2007
DOI: 10.1016/j.cardiores.2007.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled NO as a therapeutic agent

Abstract: In 1991, Frostell and colleagues reported that breathing low concentrations of nitric oxide (NO) decreased pulmonary artery pressure (PAP) in awake lambs with experimental pulmonary hypertension (PH) [Frostell C, Fratacci MD, Wain JC, Jones R, Zapol WM. Inhaled nitric oxide. A selective pulmonary vasodilator reversing hypoxic pulmonary vasoconstriction. Circulation 1991;83:2038-47]. Subsequently, efforts of multiple research groups studying animals and patients led to approval of inhaled NO by the US Food and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
101
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(106 citation statements)
references
References 93 publications
(106 reference statements)
1
101
0
4
Order By: Relevance
“…Inhaled NO gas was approved as therapeutic agent by the US Food and Drug Administration (FDA) in 1999 and the European Medicine Evaluation Agency and European Commission in 2001. It has since been used as a pulmonary vasodilator in treating pulmonary hypertension, including in patients with chronic obstructive pulmonary disease (COPD) [116,117]. However, the effect of inhaled NO on bacterial infections during these treatments was not investigated.…”
Section: Use Of No Gasmentioning
confidence: 99%
“…Inhaled NO gas was approved as therapeutic agent by the US Food and Drug Administration (FDA) in 1999 and the European Medicine Evaluation Agency and European Commission in 2001. It has since been used as a pulmonary vasodilator in treating pulmonary hypertension, including in patients with chronic obstructive pulmonary disease (COPD) [116,117]. However, the effect of inhaled NO on bacterial infections during these treatments was not investigated.…”
Section: Use Of No Gasmentioning
confidence: 99%
“…Minneci and coworkers (16) demonstrated that inhaled NO reversed the pulmonary hypertension produced by hemoglobin infusion in dogs. Many thousands of patients with acute pulmonary hypertension have been successfully treated with inhaled NO (13,33). In children with pulmonary endothelial dysfunction proved by a lack of response to acetylcholine infusion, and pulmonary hypertension following extracorporeal bypass, Wessel and coworkers (34) showed that PAP was normalized by breathing NO.…”
Section: Original Articlementioning
confidence: 99%
“…Circulating hemoglobin, both free in plasma and contained in shed microparticles, avidly scavenges NO via the dioxygenation reaction, depleting vascular NO levels and resulting in vasoconstriction (11). Because pulmonary vasoconstriction was produced in animal models by stored RBC transfusion and prevented by breathing NO (12), we previously tested whether breathing low levels of NO could selectively dilate the pulmonary circulation without producing systemic vasodilation or hypotension (13).…”
mentioning
confidence: 99%
“…23). On the one hand, idiopathic PAH in humans has been represented as an NO-deficiency disease state with the growing use of sildenafil, NO inhalation, and nebulized nitrites as therapeutic approaches in this disease (4,10,11,13,23,29,62,68). On the other hand, varying data have been reported on the relationships between eNOS expression levels and NO activity (23 and citations therein).…”
Section: Discussionmentioning
confidence: 99%